2016
DOI: 10.5539/elt.v9n5p33
|View full text |Cite
|
Sign up to set email alerts
|

Willingness to Communicate in English among Iranian EFL Students

Abstract: Much has been written on the determinants that can expedite or hinder learners' willingness to communicate in second and foreign language contexts. Though the literature is abundant with studies on many of these variables, little if any can be found to have targeted EFL students of private institutes in Iran. An effort was made in this study to examine the simultaneous impact of anxiety, self-confidence, communicative competence, and international posture on 194 Iranian EFL students' willingness to communicate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
21
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(36 citation statements)
references
References 34 publications
4
21
2
Order By: Relevance
“…Table 2 demonstrates the research studies. Self-perceived communication competence (SPCC), IP and motivation-Willingness to Communicate (WTC) (Fallah & Mashhady, 2014) Communicative language teaching (CLT), IP, WTC (Aubrey, 2010) Intrinsic-extrinsic motivation, L2 ideal selves, L2 ought-to selves, IP, Can-Do and WTC (Nishida, 2013) Proficiency, IP, L2 WTC, and other psychological constructs (Matsuoka, 2005;Yashima, 2009) L2 learning and L2 communication variables in the, WTC, IP (Yashima, 2002) IP, WTC and Second Language Communication (Yashima, et al,2004) WTC -Self-confidencelearners attitude (IP) -motivation (Hashimoto, 2002;Peng, 2007;Şener, 2014) IP and WTC (Asmalı, 2016;Aliakbari, Kamangar, & Khany, 2016;Collins, 2013;Mahmoodi, Ghafoori & Amini, 2013;Piggin, 2010;Ulu, Weiwei, & Yu, 2015;Mystkowska-Wiertelak & Pietrzykowska, 2011) The research of Asmalı (2016) examined the relationship among willingness to communicate and some variables such as students' motivation to learn English, their confidence for communication in English and their motivation to learn English. The findings suggested that these variables were found to be related to their WTC in English.…”
Section: International Posturementioning
confidence: 99%
“…Table 2 demonstrates the research studies. Self-perceived communication competence (SPCC), IP and motivation-Willingness to Communicate (WTC) (Fallah & Mashhady, 2014) Communicative language teaching (CLT), IP, WTC (Aubrey, 2010) Intrinsic-extrinsic motivation, L2 ideal selves, L2 ought-to selves, IP, Can-Do and WTC (Nishida, 2013) Proficiency, IP, L2 WTC, and other psychological constructs (Matsuoka, 2005;Yashima, 2009) L2 learning and L2 communication variables in the, WTC, IP (Yashima, 2002) IP, WTC and Second Language Communication (Yashima, et al,2004) WTC -Self-confidencelearners attitude (IP) -motivation (Hashimoto, 2002;Peng, 2007;Şener, 2014) IP and WTC (Asmalı, 2016;Aliakbari, Kamangar, & Khany, 2016;Collins, 2013;Mahmoodi, Ghafoori & Amini, 2013;Piggin, 2010;Ulu, Weiwei, & Yu, 2015;Mystkowska-Wiertelak & Pietrzykowska, 2011) The research of Asmalı (2016) examined the relationship among willingness to communicate and some variables such as students' motivation to learn English, their confidence for communication in English and their motivation to learn English. The findings suggested that these variables were found to be related to their WTC in English.…”
Section: International Posturementioning
confidence: 99%
“…Learners with a high level of willingness to communicate tend to be very active and engaged in language learning activities and this leads to taking much more advantages of the presented materials in the class; this is proved in reviewing the related literature. (e.g., Rahbar,Suzani, and Sajadi, 2016;Bergil, 2016;Fahim and Dhamotharan, 2016;Aliakbari, Kamangar, and Khany, 2016). Hence, it is of utmost importance to pinpoint the factors that influence WTC of language learners as in this way, they use language in a more communicative way.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the very recent study of Aliakbari, Kamangar and Khany (2016) found that the most powerful predictor of L2 WTC is communicative competence which is not in line with the above-mentioned Iranian recent studies as well as the other previous EFL/ESL important studies, (such as Yashima, 2002;Clément et al, 2003). Aliakbari and Mohsennejad (2014) explained that the rationale behind the odd finding of the study could pertain to the nature of the participants as teenagers possessing a false self-confidence.…”
Section: Literaturementioning
confidence: 59%